Unnatural Pet-Keeping: Pet-Custody Disputes in the Aftermath of Hurricane Katrina - Zelinger, Amir (Humanimalia, 2018)
This paper embeds pet-keeping into the scholarship on Hurricane Katrina. Recent research into Hurricane Katrina has mostly emphasized the social significance of this natural disaster, maintaining that issues of class, race, and social inequality were responsible for the extent of the catastrophe and for the fact that certain populations suffered much more severely than others. Focusing on custody disputes over pets that were stranded during the catastrophe and adopted by new owners outside of the area affected, this paper argues that the social conflicts at the root of Katrina extended to the realm of pet-keeping. It contends that in the same way that Katrina brutally lay bare some of the most burning social conflicts plaguing American society, it also revealed, as no other event could, the entanglement of pet-keeping within these conflicts. Thus, Hurricane Katrina made clear that pets are not simply part of American society—they are also part of the hierarchies, inequalities, and discriminations this society is structured upon.